Paraventricular Cavernous Malformation - Idarraga Vanegas, Esteban (Revista Argentina de Neurocirugía, 2021)
Introduction: Cavernous malformation represents among 5 to 13% of brain vascular malformations, most of them have a supratentorial location. Clinically they can remain asymptomatic or present neurological symptoms. In cavernomas with recurrent hemorrhage, located in safe areas ,surgical resection is the treatment of choice. However for those which have a deep yuxta ventricular localization it is necessary to know the relationship between the lesion and eloquent cerebral structures. Fiber tractography and intraoperative navigation systems are essentials tools to plan and guide the surgical approach and make a mapping of the projection, association and commissural fibers in order to have a safe access to the lesion. Objective: To describe the surgical technique using neuronavigation for the resection of a right frontal yuxta ventricular cavernous malformation through a minimal approach. Case A 20 year old man, professional athlete with left arm paresthesia and severe headache. Magnetic resonance shows an heterogeneous lesion in T1 and T2 with a hemosiderin in the roof of the right lateral ventricle, compatible with a cavernous malformation. Its size was 28 mm x 31mm x 28 mm in the transversal, dorsoventral and rostrocaudal diameter. The fiber tractography shows an intimate relationship with the corticospinal tract on its path through the corona radiata. Results: Complete resection of the lesion. The patient evolved without a neurological deficit and was discharged 72 hours later. Conclusion: The fiber tractography and the intraoperative navigation system allow the deep lesions approach, especially for those who have an intimal relationship with eloquent´s areas, using minimally corticotomy with less parenchymal retraction.